Triphenylamine-styryl-anthracene derivative without thermal fluorescence quenching property for spectrally stable organic/inorganic hybrid light emitting diodes with no UV residue. (December 2021) - Huang, Jia; Zhou, Nonglin; Shao, Xiaona; Xun, Fang; Zhang, Jiayan; Lin, Hongwei
Abstract: Herein, the organic blue emitting material ( E )-4-(4-(anthracen-9-yl)styryl)- N, N -diphenylaniline (AnStDPA ) with D–π–A chromophore was synthesized. The thermal, optical, electrochemical properties and the device performance of the AnStDPA were investigated. The AnStDPA shows high thermal stability with decomposition temperature ( T d, 5% weight loss) value of 319 °C, high photoluminescence quantum yield (PLQY) with value of 0.92 and no thermal fluorescence quenching property. The HOMO and LUMO level of AnStDPA are −5.44 eV and −2.60 eV, respectively. When using AnStDPA to construct organic/inorganic hybrid LED, the LED exhibits blue emission, stable Commission Internationale de L'Eclairage (CIE) chromaticity coordinate of (0.1522, 0.0895) and tranquil luminance efficiency of 10 lm W −1 (around) at various currents. In addition, the phosphor-free hybrid WLEDs based on AnStDPA and Rubrene (5, 6, 11, 12-tetraphenylnaphthacene) were prepared. The device possesses luminance efficiency of 27.70 lm W −1 (at 19.90 mA), CCT of 4363 K, Ra of 65.2, and CIE chromaticity coordinate of (0.3471, 0.2750). Moreover, there is almost no ultraviolet (UV) residue in these hybrid LEDs based on the AnStDPA . We have simultaneously achieved organic/inorganic hybrid blue LED (based on near UV chip) with almost no UV residue and spectral stability. Highlights: The AnStDPA possesses high PLQY and no thermal fluorescence quenching property. The spectral overlap between the absorption of AnStDPA and emission from NUV chip. The CIE of the blue hybrid LED based on AnStDPA is stable at various currents. The phosphor-free hybrid WLED based on AnStDPA and Rubrene was studied. There is almost no UV residue in these hybrid LEDs based on the AnStDPA.